Socio-economic overview of long-lived companies in Zone 1, Northeast Ecuadorian - Ojeda Zambrano, Carla de los Ángeles (SATHIRI, 2025)
The corporate and economic structure of long-lived active companies (over 25 years old) within Zone 1 of the territorial planning of Ecuador in 2023 covers a great diversity in various aspects. To analyze this dynamic, a cross-sectional descriptive study with an inductive and quantitative basis was conducted through documentary compilation in official databases. After analyzing 132 organizations, the research revealed that none of them have existed for over a century. Furthermore, the most common company size corresponds to microenterprises. This indicates a low level of growth not only in their total income but also in their organizational structure.